Variable-, fractional-order digital filter - application - Duch, Piotr; Bąkała, Marcin; Sankowski, Dominik; Ostalczyk, Piotr (Wydawnictwo Politechniki Łódzkiej, 2014)
[...] This chapter is organised as follows. First, in Section 2 fundamental definition of the VFOBD is given. Next the VFO-DF fundamental structure is proposed. In Section 3 two equivalent descriptions of the VFO-DF a filter response is presented. Finally in Section 4 the VFO-DF responses is evaluated and compared to the filtering effects of the classical first-order linear filter.[...]
Keywords: filtry cyfrowe; zmienny filtr cyfrowy rzędu ułamkowego; różnica wsteczna o zmiennej ułamkowej kolejności; digital filter; variable fractional-order digital filter; variable-, fractional-order backward difference; VFO-DF; VFOBD